Capital incentive policies in the age of cloud computing An empirical case study - Andres, Raphaela (OECD Science, Technology and Industry Working Papers, 2020)
This paper assesses whether current policy environments are appropriate for the emergence of cloud computing technology. In particular, this research uses firm level data for Germany and the United Kingdom to examine the impact of capital incentive programmes (a common policy present in most OECD countries) on cloud adoption. The design for many of these policies target investments in physical capital while excluding digital services like the cloud. Firms view digital investments and digital services as substitutes, therefore narrowly defined incentive programmes may actually discourage the use of emerging tools like cloud computing, which are found to enable the growth and performance of young entrants. Overall, the results find that while capital incentive policies encourage firm investments in ICT and other forms of capital, they actually reduce the probability of cloud adoption. Policy makers may therefore need to reconsider the design of capital incentive programmes within their jurisdictions